Scientific-methodological knowledge and its development in the educational process - S. A. Gilmanov; A. V. Mironov; V. A. Mishchenko (Russian State Vocational Pedagogical University, 2024)
Introduction. For students, mastering the methodological foundations of scientific research plays an important role in professional education, providing scientifically proven support for professional thinking and readiness to scientifically substantiate the practical activities of a specialist to form a mechanism for intellectual and personal self-development. Today, numerous educational literature is being published, and educational disciplines devoted to the methodology of science and scientific research are being introduced. However, in most of the educational and scientific works created by students (course projects, final qualification papers, etc.), methodological provisions are formulated with errors; descriptions of the organisation of research, interpretation and design of their results are unsatisfactory. Therefore, there is the problem of finding ways to improve methodological literacy, methodological competence, and methodological culture of students. The relevance of such research is conditioned by the need to study the causes of such a situation, to develop ways for improving student methodological competence, to highlight and summarise the experience of teaching methodological knowledge, and to suggest ways for improving the educational process. The solution to this problem is especially significant for the humanities specialists (in particular, for educators and psychologists), who deal with the influence on the personality and human consciousness included in the social regulation of human behaviour.                Aim. The present research aims to: 1) substantiate the theoretical approach to the scientific and methodological support of the process of mastering the methodological foundations of scientific research by students as to the development of scientific-methodological knowledge (SMK) based on the analysis of scientific and educational literature, the practice of teaching disciplines aimed at studying the methodological aspects of psychological and pedagogical research; 2) to identify the main guidelines for improving the ways to support the formation of SMK using examples from empirical studies of its development by students in the educational process, from the generalisation of the practical experience of the authors.                Methodology and research methods. The research methodological framework was based on the approaches of Russian scientists to the methodological foundations of science and scientific research as a holistic knowledge, in which principles, norms, methods and scientific and cognitive activity are developed at the philosophical, general scientific, concrete scientific, methodical levels. Analysis, generalisation and systematisation were used as theoretical research methods; testing, survey, included observation and generalisation of experience were applied as empirical methods. To prove the propositions put forward by the authors, four empirically verifiable hypotheses were formulated. Two of them were confirmed: one was partially confirmed; the second one (about the absence of a connection between direct and remote forms with the formation of SMK) was not confirmed. In the mathematical and statistical interpretation of individual research results (correlation and variance types of analysis), the IBM SPSS Statistics 23 was employed.                Results. The guidelines for supporting the development of SMK by students in the educational process were outlined: reliance on the creation of a research project by the trainee; placing the trainees in the position of an independent researcher; developing an understanding of the content and scope of the key concepts of research, its unity and integrity; paying special attention to the transformation of information and its presentation in various forms.                Scientific novelty. The authors proposed and substantiated the idea of the study of the research methodological foundations as the development of SMK, which equips the researcher with an arsenal of guidelines, means and methods of action, providing the closest possible approach to the truth in the search for new scientific knowledge.                Practical significance. The proposed approaches to the development of SMK can be used in the practice of studying disciplines devoted to the research methodological foundations in the social sciences and humanities, in support of students' course projects and final qualifying works.